TOWARD AN OBJECTIVE METHOD TO CLASSIFY TREMOR DOMINANT AND POSTURAL INSTABILITY AND GAIT DIFFICULTY SUBTYPES OF PARKINSON'S DISEASE: A PILOT STUDY - Rezvanian, Saba; Lockhart, Thurmon; Frames, Christopher; Soangra, Rahul (Biomedical sciences instrumentation, 2017)
Discriminating the two subtypes of tremor dominant (TD) and postural instability/gait difficulty (PIGD) in Parkinson's disease (PD) at early stage is highly valuable and crucial for progression treatment of disease for caregivers. However, there is no objective method or a subtype-specific biomarker yet available for identifying these two subtypes. A computational approach in frequency domain could be a good candidate to introduce biomarker since PD tremor had frequency range of 3-7 Hz. By using frequency component of the whole body Center Of Pressure (COP) signal, we propose a ratio between high and low frequency range. To evaluate this ratio, COP data of ten PD patients were utilized. The results suggest that identifying PD subtypes is attainable by using the frequency information of COP signals.